Tuzūkāt-i Tīmūrī as a Source on Chagatai Military Tactics, Late Fourteenth to Early Fifteenth Centuries - Leonid A. Bobrov; Aibolat K. Kushkumbayev; Zhaksylyk М. Sabitov; Myltykbayuly (Oriental Studies)
Introduction. The article examines some historical and other related circumstances behind the creation of Tuzūkāt-i Tīmūrī (The Code of [Amir] Timur). Goals. The paper seeks to identify the narrative’s place in a variety of written sources on Chagatai military tactics of the late fourteenth to early fifteenth centuries. Results. The study discovers The Code is a composite work compiled from a text allegedly found in Arabia by Abu TalibTurbati in the early seventeenth century, subsequent comments of a translator and a copyist, some fragments of Timurid writings dated from the early fifteenth century, and corrections introduced by the Mughal historian Muhammad Ashraf Bukhari. The final version of Tuzūkāt-i Tīmūrī was completed between the mid-1620s and 1650s at the earliest. The sections about tactics of Amir Timur’s Chagatai army are very likely a combination of messages borrowed by the compilers from fifteenth-century Timurid written sources — and their own interpretations of Safavid (and possibly Mughal) combat practices of later times. Descriptions of combat formations and tactical techniques contained in Tuzūkāt-i Tīmūrī cannot be merely extrapolated to military realities of Amir Timur’ era. However, the narrative does clarify some specifics of Chagatai combat tactics mentioned in the Timurid Zafarnamas (ones by Nizam al-Din Shami and Sharaf ad-Din Ali Yazdi). Some of the descriptions are not that clear to contemporary researchers while those were obvious enough to the seventeenth-century authors. For this reason, The Code can be most instrumental in ‘deciphering’ some complicated or controversial patterns of tactics contained in Timurid sources of the late fourteenth and early fifteenth centuries. Conclusions. It is possible to highlight data pertaining to Chagatai combat tactics of the designated period through comparing the text of Tuzūkāt-i Tīmūrī to those of early fifteenth-century Zafarnamas and other works of the Timurid era.